2019
DOI: 10.1111/joa.13061
|View full text |Cite
|
Sign up to set email alerts
|

Glia to neuron ratio in the posterior aspect of the human spinal cord at thoracic segments relevant to spinal cord stimulation

Abstract: Spinal cord stimulation (SCS) applied between T8 and T11 segments has been shown to be effective for the treatment of chronic pain of the lower back and limbs. However, the mechanism of the analgesic effect at these medullary levels remains unclear. Numerous studies relate glial cells with development and maintenance of chronic neuropathic pain. Glial cells are electrically excitable, which makes them a potential therapeutic target using SCS. The aim of this study is to report glia to neuron ratio in thoracic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…We found that glia outnumbered neurons (20 to 1) in this section of the cord. 12 These results imply that when an electrical field is applied to the dorsal aspect of the cord, it affects both neuron and glial cells and thus the ability to modulate the homeostatic milieu resulting from neuroglial interactions.…”
Section: Introductionmentioning
confidence: 97%
“…We found that glia outnumbered neurons (20 to 1) in this section of the cord. 12 These results imply that when an electrical field is applied to the dorsal aspect of the cord, it affects both neuron and glial cells and thus the ability to modulate the homeostatic milieu resulting from neuroglial interactions.…”
Section: Introductionmentioning
confidence: 97%
“…Although neurons and glial cells are the main cellular constituents of neural tissue, glial cells are more abundant than neurons in the spinal cord of primates, including humans. 2 4 Among spinal glia, microglia and astrocytes are known to be integral to the establishment and maintenance of neuropathic pain. 5 7 Our group previously reported on the distinctive response of glia and neurons when exposed to different electrical signals, 8 , 9 demonstrating that electrical stimulation of the spinal cord may be used to differentially modulate those cells and provide improved relief of neuropathic pain in an animal model.…”
Section: Introductionmentioning
confidence: 99%
“… Further examination of optimal lead selection, lead position, and parameters of stimulation. Target region: T9–T10; non-neuronal cells in the nervous system Ruiz-Sauri 2019 72 Dissection of posterior spinal cord segments from 11 human cadavers. Glial to neuronal ratio in posterior gray matter within the T8– T11 vertebral region ranges from 11:1 to 13:1.…”
Section: Introductionmentioning
confidence: 99%
“… 71 Basic science research has indicated that glial cells outnumber neurons in the spinal cord 20:1, are electrically excitable, and have the ability to modulate ascending pain pathways. 72 , 73 This evidence allowed researchers to hypothesize that SCS parameters can be adjusted to differentially target neurons and glial cells in order to maximize the efficacy of treatment. 64 …”
Section: Introductionmentioning
confidence: 99%